2022
DOI: 10.3390/su142416938
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Response of Tropical Catchments to Climate Change as Modeled by the GR2M Model: A Case Study in Costa Rica

Abstract: This study aimed to assess the impacts of climate change on streamflow characteristics of five tropical catchments located in Costa Rica. An ensemble of five General Circulation Models (GCMs), namely HadGEM2-ES, CanESM2, EC-EARTH, MIROC5, MPI-ESM-LR dynamically downscaled by two Regional Climate Models (RCMs), specifically HadRM3P and RCA4, was selected to provide an overview of the impacts of different climate change scenarios under Representative Concentration Pathways (RCPs) 2.6, 4.5 and 8.5 using the 1961–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…These previous studies do not characterize daily variability from the models. In particular, the most recent study by Mendez et al (2022) which analyzed climate change hydrological projections for 5 selected Costa Rican subbasins is different to our study, not only in the details of datasets used, but also in a very fundamental way as the authors used monthly instead of daily data and the delta downscaling method they applied consisted in shifting the observational dataset variability with a perturbation of the future monthly GCM-RCM anomalies with respect to the baseline period. This is different to the application of the daily downscaling method that we are presenting, which is based in conserving the daily variability of the bias-corrected GCMs.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…These previous studies do not characterize daily variability from the models. In particular, the most recent study by Mendez et al (2022) which analyzed climate change hydrological projections for 5 selected Costa Rican subbasins is different to our study, not only in the details of datasets used, but also in a very fundamental way as the authors used monthly instead of daily data and the delta downscaling method they applied consisted in shifting the observational dataset variability with a perturbation of the future monthly GCM-RCM anomalies with respect to the baseline period. This is different to the application of the daily downscaling method that we are presenting, which is based in conserving the daily variability of the bias-corrected GCMs.…”
Section: Introductionmentioning
confidence: 77%
“…It is important to note that floods studies in tropical regions are generally scarce (some exceptions in Asia can be found in Das et al, 2022;Pandey et al, 2022;Mahato et al, 2022), and in Central America the availability of regional/country studies is even rarer (for Costa Rica see Mendez et al, 2022). In higher and mid latitudes, the main control on hydrology can be related to other physical processes, for example snow, which produces a very different streamflow seasonal cycle (and flood characteristics) compared to places without snow, as in the former case the precipitation is stored as snow during the winter and released in a smoother peak during the spring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that, it must be managed and quantified by the implementation of tools that could help decision-support and management processes. Among these tools, hydrological models have emerged over the last thirty years [1][2][3][4][5][6][7], particularly models of rainfall-runoff transformation, recharge, and evaporation [8][9][10]. The primary focus of hydrological modeling is to reproduce the flows with the smallest possible error.…”
Section: Introductionmentioning
confidence: 99%